Biaya Produksi: Pengertian, Struktur Biaya Langsung dan Tidak Langsung, Perhitungan Harga Pokok, Unsur-Unsur Harga Pokok dan Jenisnya - Andri Wijaya Panjaitan; Marzuti Isra; Muhammad Hafizon Fatoni; Putri Fazirah Rahman; Petrus Watcahya Pemilulius; Rico Raparendi; Angga Surya Darma (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
oil palm plantations are one of Indonesia's leading agricultural sectors and contribute significantly to the economy. In production activities, costs are an important factor for a company's efficiency and profitability. This study discusses the structure of production costs, the division of direct and indirect costs, and the method of calculating the Cost of Goods Sold (HPP) in oil palm nurseries and production units. The main objective is to provide a comprehensive understanding of production cost management to achieve more efficient and effective cost management for oil palm plantations.